The Potential of Methocinnamox as a Future Treatment for Opioid Use Disorder: A Narrative Review - Colleen G. Jordan; Amy L. Kennalley; Alivia L. Roberts; Kaitlyn M. Nemes; Tenzing Dolma; Brian J. Piper (MDPI AG, 2022)
The opioid epidemic is an ongoing public health crisis, and the United States health system is overwhelmed with increasing numbers of opioid-related overdoses. Methocinnamox (MCAM) is a novel mu opioid receptor antagonist with an extended duration of action. MCAM has potential to reduce the burden of the opioid epidemic by being used as an overdose rescue treatment and a long-term treatment for opioid use disorder (OUD). The currently available treatments for OUD include naloxone, naltrexone, and methadone. These treatments have certain limitations, which include short duration of action, patient non-compliance, and diversion. A narrative review was conducted using PubMed and Google Scholar databases covering the history of the opioid epidemic, pain receptors, current OUD treatments and the novel drug MCAM. MCAM could potentially be used as both a rescue and long-term treatment for opioid misuse. This is due to its pseudo-irreversible antagonism of the mu opioid receptor, abnormally long duration of action of nearly two weeks, and the possibility of using kappa or delta opioid receptor agonists for pain management during OUD treatment. MCAM's novel pharmacokinetic and pharmacodynamic properties open a new avenue for treating opioid misuse.